Integration of Islamic Values in Madrasah Ibtidaiyah Teacher Education (PGMI) Learning to Prepare the Generation of Society 5.0 - Afina Wastyanti; Ari Susetiyo (Action Research Journal Indonesia (ARJI), 2025)
This study discusses Teacher Education Madrasah Ibtida'iyah integration of Islamic values in learning. Madrasah Ibtidaiyah Teacher Education (PGMI) is an important strategy to prepare the noble 5.0 generation of society in the midst of technological progress and a shift in social values. This study aims to examine the integration approach of Islamic values in PGMI learning through literature review, focusing on the development of value-based curriculum, learning methods, implementation challenges, and reinforcement strategies. The literature review analyzes books, scientific journals, and official reports related to PGMI and Society 5.0. The results showed that the integration of Islamic values is effective through interdisciplinary approaches, exemplary lecturers, and the use of technology. Key challenges include the limited digital literacy of lecturers, resistance to modern curricula, and the influence of digital Culture. Strengthening strategies include lecturer training, contextual curriculum revisions, and collaboration with the community. This study concludes that the integration of Islamic values in PGMI needs to be optimized to produce MI teachers who are able to form a moral generation.